Friendships Between LGBT Individuals and Heterosexuals: Voices from Indonesian Youth - Yudi, Christopher; Novitareri, Aurelia Stella; Prayogi, Gita Salsabilla Ike Putri; Setyawan, Jefri (Journal of Psychological Perspective, 2025)
LGBT (lesbian, gay, bisexual and transgender) individuals face various social challenges, including discrimination and pressure that affect their ability to build interpersonal relationships, especially with heterosexual individuals. This study aims to explore the friendship dynamics between gay and lesbian individuals and heterosexuals, focusing on social experiences and interactions among young Indonesians. This qualitative research used a phenomenological approach with semi-structured interviews, and the data were thematically analyzed. Three participants, namely gay, lesbian, and heterosexual individuals, were selected through purposive sampling. The results showed that Indonesian society still has difficulty accepting sexual orientations that differ from heterosexuals, with the self-internalized stigma on LGBT individuals further limiting their freedom to express their sexual identity. However, solidarity across sexual orientations is visible, especially among young people, who are more open to sexual diversity, although their attitudes vary. This research emphasizes the importance of social acceptance in reducing discrimination and creating inclusive spaces for LGBT individuals.Abstrak: Individu LGBT (lesbian, gay, biseksual, dan transgender) menghadapi berbagai tantangan sosial, termasuk diskriminasi dan tekanan yang mempengaruhi kemampuan mereka dalam membangun hubungan interpersonal, terutama dengan individu heteroseksual. Penelitian ini bertujuan untuk mengeksplorasi dinamika pertemanan antara individu gay dan lesbian dengan heteroseksual, dengan fokus pada pengalaman sosial dan interaksi di kalangan orang muda Indonesia. Penelitian kualitatif ini menggunakan pendekatan fenomenologi dengan wawancara semi-terstruktur, kemudian data dianalisis secara tematik. Tiga partisipan, yaitu individu gay, lesbian, dan heteroseksual dipilih melalui purposive sampling. Hasil penelitian menunjukkan bahwa masyarakat Indonesia masih kesulitan menerima orientasi seksual yang berbeda dari heteroseksual, dengan adanya stigma internal pada individu LGBT yang semakin membatasi kebebasan mereka dalam mengekspresikan identitas seksual. Meski demikian, solidaritas lintas orientasi seksual terlihat, terutama di kalangan generasi muda yang lebih terbuka terhadap keberagaman seksual, meskipun sikap mereka bervariasi. Penelitian ini menekankan pentingnya penerimaan sosial dalam mengurangi diskriminasi dan menciptakan ruang inklusif bagi individu LGBT.